The Mini-EUSO telescope on board the ISS: in-flight operations and performances. Issue 1 (1st November 2022) - Marcelli, L; Battisti, M; Belov, A; Bertaina, M; Cambiè, G; Capel, F; Casolino, M; Ebisuzaki, T; Fuglesang, C; Klimov, P; Parizot, E; Picozza, P; et al.
Abstract : Mini-EUSO is a high sensitivity imaging telescope that observes the Earth from the ISS in the ultraviolet band (2904÷430 nm), through the UV-transparent window in the Russian Zvezda module. The instrument, launched in 2019 as part of the ESA mission Beyond, has a field of view of 44°, a spatial resolution on the Earth surface of 6.3 km and a temporal resolution of 2.5 microseconds. The telescope detects UV emissions of cosmic, atmospheric and terrestrial origin on different time scales, from a few microseconds upwards. Mini-EUSO main detector optics is composed of two Fresnel lenses focusing light onto an array of 36 Hamamatsu multi-anode photomultiplier tubes, for a total of 2304 pixels. The telescope also contains: two ancillary cameras to complement measurements in the near infrared and visible ranges, an array of Silicon-PhotoMultipliers and UV sensors to manage night-day transitions. In this work we will describe the in-flight operations and performances of the various instruments in the first months after launch.